2020
DOI: 10.1097/spv.0000000000000918
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perceptions on Surgical Care Suspension for Pelvic Floor Disorders During the COVID-19 Pandemic

Abstract: Objectives The primary objective of the study was to evaluate patients’ attitudes toward the postponement of their scheduled procedures for pelvic floor disorders (PFD) because of the COVID-19 pandemic. Secondary objectives were to identify patients who were upset with the postponement of their PFD procedures and to identify factors that are associated with being upset because of the delay in care. Methods This was a cross-sectional, survey-based study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Furthermore, patients who reported being unhappy were more likely to report feelings of isolation and anxiety because their surgery was postponed. 12 In another study involving patients with lung cancer, 9.1% (N=15) of patients postponed their treatment during the COVID-19 pandemic because of pandemicrelated anxiety. 13 With the goal of improving care at our institution, we conducted a brief institutional review board-approved survey to evaluate how postponing MMS treatment due to the COVID-19 pandemic affected patients.…”
Section: Practice Pointsmentioning
confidence: 99%
“…Furthermore, patients who reported being unhappy were more likely to report feelings of isolation and anxiety because their surgery was postponed. 12 In another study involving patients with lung cancer, 9.1% (N=15) of patients postponed their treatment during the COVID-19 pandemic because of pandemicrelated anxiety. 13 With the goal of improving care at our institution, we conducted a brief institutional review board-approved survey to evaluate how postponing MMS treatment due to the COVID-19 pandemic affected patients.…”
Section: Practice Pointsmentioning
confidence: 99%
“…One study found that patients whose prolapse surgery was postponed during the pandemic experienced depressed mood as a result of their symptoms, fear that delayed care would worsen their condition, and anxiety over surgery postponement 10 . Following a survey that assessed the quality of life in women with pelvic floor disorders, the majority reported that their disorder remained equally relevant or became more significant during the pandemic 11 .…”
Section: Discussionmentioning
confidence: 99%
“…One study found that patients whose prolapse surgery was postponed during the pandemic experienced depressed mood as a result of their symptoms, fear that delayed care would worsen their condition, and anxiety over surgery postponement. 10 Following a survey that assessed the quality of life in women with pelvic floor disorders, the majority reported that their disorder remained equally relevant or became more significant during the pandemic. 11 Another study found that patients with more advanced prolapse (stage III/IV) reported a decreased quality of life caused by progression of their symptoms when compared to patients with earlier stages of prolapse (stage I/II).…”
Section: Discussionmentioning
confidence: 99%
“…( Kimmig et al, 2020 , Bartlett et al, 2020 Jun , Finley et al, 2020 May 1 ) Additional research has focused upon patient perception of surgical delay, and willingness to reschedule surgery. ( Brown et al, 2020 , Sii et al, 2020 Oct ) A study investigating patients’ attitudes towards the postponement of scheduled procedures for pelvic floor disorders discovered that up to half of patients were upset by the delay in their care ( Mou et al, 2020 ), but did not quantify the impact on patient psyche. Research has determined when faced with delay in ovarian cancer care due to the COVID-19 pandemic, 51.4 % of patients experienced borderline or abnormal anxiety, and 88.6 % experienced significant worry.…”
Section: Discussionmentioning
confidence: 99%